2006
DOI: 10.1080/10550490601000504
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Characteristics and Antisocial Personality Disorder of Early and Late Onset Alcoholics Identified in a Primary Care Clinic

Abstract: A total of 1,734 persons were prospectively screened in a primary care clinic to examine the demographic characteristics and presence or absence of antisocial personality disorder among early onset alcoholics (EOA) and late onset alcoholics (LOA). A total of 76 EOA (male = 58 and female = 18) and 80 LOA (male = 56 and female = 24), as determined by the Comprehensive Drinking Profile Scale, participated in the study. EOA tended to be single and were younger, in a lower socioeconomic class, raised by non-biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…PD was also associated with single marital status, individuals who were not raised by their parents during childhood, introverted personalities, first visits, and those seeking for psycho-counseling treatment. Prior findings (Phillips and McElroy 2000; Huang et al 2006; Bouchard et al 2009) regarding characteristics of PD were confirmed as well. These features are useful in identifying PD in subgroups and further understanding the pathogenesis of PD.…”
Section: Discussionsupporting
confidence: 60%
“…PD was also associated with single marital status, individuals who were not raised by their parents during childhood, introverted personalities, first visits, and those seeking for psycho-counseling treatment. Prior findings (Phillips and McElroy 2000; Huang et al 2006; Bouchard et al 2009) regarding characteristics of PD were confirmed as well. These features are useful in identifying PD in subgroups and further understanding the pathogenesis of PD.…”
Section: Discussionsupporting
confidence: 60%
“…Irwin's study [33] concerning only males reported that 40% of subjects had an annual income of less than 20 000 dollars, despite their having acquired a high level of education. The study by Huang et al [82] reported that 37% of alcohol-dependent subjects fell into the lowest socio economic classes. Better financial resources were associated with a better prognosis for both alcohol dependence and psychosocial outcomes in the three-year follow-up study by Moos and Moos [27].…”
Section: Discussionmentioning
confidence: 99%
“…Both studies, in which the determinants of this positive evolution could be identified, the reduction of legal problems was reported to be the result of treatment interventions and reductions in substance use [80,81], Legal problems were frequently associated with alcohol dependence: this association was reported 17 times. There was some evidence to suggest that legal problems may be associated with an earlier age of onset of alcohol dependence [82,83]. Other dependence was associated with legal problems three times in two studies [82,84],…”
Section: Legal Problem S (Not Classified In Th E Icf)mentioning
confidence: 99%
See 1 more Smart Citation